Shadowing the Latin Monetary Union: Monetary regimes and interest rates in the Balkan periphery (1867-1912) - Nikolaj Nenovski; Jacques-Marie Vaslin (The Journal of European Economic History, 2020)
In this study we reconstruct the Balkan countries' monetary relations with Western Europe in the period of the Latin Monetary Union (LMU), particularly from 1867 to 1912. We concentrate on the complex puzzle of LMU and its relations with the Balkans within the theoretical framework of dependent capitalism, reduced to "the incompatibility hypothesis", based on which we analyse the dynamics of interest rates on the Balkan countries' foreign debt. Our original monthly database (1875-1912) shows that the Balkan countries wishing to join the LMU at the end of the 19th century were asymmetric in relation to the core countries (France, Italy, Belgium and Switzerland). Their incorporation into the LMU created an agio between gold and silver. Monetary union required a policy of stringency in the Balkan countries if they were to converge toward the core, but their remoteness from the centre (both geographical and economic) consigned them to the periphery.
Keywords: 330